2020
DOI: 10.3390/su12155956
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pollution Related Deficiencies Identified through PSC Inspections for the Period 2014–2018

Abstract: The aim of this paper is to analyze the available data on recorded ship deficiencies during ship inspections which are related to pollution prevention. The purpose of these inspections regulated under the different Port State Control (PSC) regimes’ Memorandum of Understanding (MoUs), is to detect and disable the operation of substandard ships. The data obtained were sorted according to the six Annexes of the International Convention for the Prevention of Pollution from Ships (MARPOL) Convention, and a comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Wang et al (2021) found that the biggest deficiencies in ship detentions during Tokyo MoU PSC inspections were caused by fire safety and navigational safety, using a Bayesian network model. Yang In addition, data mining (Tsou, 2019;Xiao et al, 2021;Sevgili & Töz, 2022) and statistical analysis studies (Arslan & Eyigün, 2016;Farag, 2016;Bolat, 2019;Ukić Boljat et al, 2020;Mantoju, 2021;Prieto et al, 2021;Şanlıer, 2020Kostović, et al, 2022, Turna & Öztürk, 2023Uçar & Boran, 2023) have also been carried out. Tsou (2019) There are also studies on the legal dimension of port state control (Keselj, 1999;Stoyanov & Terlemesian, 2004;Bang & Jang, 2012; and studies on stakeholders (Piniella et al, 2020;Nwokedi et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al (2021) found that the biggest deficiencies in ship detentions during Tokyo MoU PSC inspections were caused by fire safety and navigational safety, using a Bayesian network model. Yang In addition, data mining (Tsou, 2019;Xiao et al, 2021;Sevgili & Töz, 2022) and statistical analysis studies (Arslan & Eyigün, 2016;Farag, 2016;Bolat, 2019;Ukić Boljat et al, 2020;Mantoju, 2021;Prieto et al, 2021;Şanlıer, 2020Kostović, et al, 2022, Turna & Öztürk, 2023Uçar & Boran, 2023) have also been carried out. Tsou (2019) There are also studies on the legal dimension of port state control (Keselj, 1999;Stoyanov & Terlemesian, 2004;Bang & Jang, 2012; and studies on stakeholders (Piniella et al, 2020;Nwokedi et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, Jiayu Bai and Chenxing Wang [35] propose that regional PSC MoUs should include ships navigating in polar waters, especially ocean-going fishing ships operating in polar waters, to ensure the safety of navigation in polar regions and the compliance of ships with pollution prevention requirements. Helena Uki'c Boljat et al [36] used the inspection records of PSC MoUs around the world from 2014 to 2018 to compare and analyze the deficiency records of PSC inspections of the MARPOL Convention and its six appendices through statistical chi-squared tests and correlation analysis. The data are used to determine the common deficiencies of the world fleet in the prevention of pollution from ships to suggest that the PSC MoU in each region strengthen the PSC inspection deficiency.…”
Section: Other Literature On Exploring Pscmentioning
confidence: 99%
“…It has the longest and most stable CIC implementation experience and has experience working with Tokyo MoU to implement CIC for the same series of deficiency items [2]. In addition, the deficiency database of Paris MoU has been used by a number of scholars in PSC studies (Yu, Q. et al [30], Boljat, H. U. et al [36], Liu, K. Z. et al [19], Bruin, G. J. et al [9], Akyurek, E. and P. Bolat [44], Dinis, D. et al [12], Akyurek, E. and P. Bolat [45], Chen, Y. L. et al [27]). So, using Paris MoU's Key Performance Indicators (KPIs) as the source of data (Table 2), we compiled six categories, including time of occurrence, deficiency code, ship type, flag state, inspection agency, and inspection location, from 1 November 2018 to 31 October 2021 (36 months).…”
Section: Information Collationmentioning
confidence: 99%
“…Qualitative research Mixed methods research Navas de Maya et al 28 , Osman et al 47 , Fu et al 49 , Yan et al 52 , Xiao et al 62 , Dikis et al 64 , Yang et al 67 , Yu et al 68 , Ukic ´Boljat et al 69 , Liu et al 70 Xiao et al 5 , Piniella et al 6 , Akyurek and Bolat 32 , Liou et al 34 , Osman et al 36 , Bielic ´et al 39 , Randic ´et al 45 , Akyurek and Bolat 71 , Knapp and van de Velden 72 , Chi and Jun 73 Cebi et al 4 , Yang et al 23 , Lin and Cheng 29 , Wang et al 33 , Sotiralis et al 35 , Graziano et al 38 , Wu et al 54 , Knapp and Franses 63 , Fu et al 74 , Cariou et al 75 Figure 12. The number of papers per year by the research fields.…”
Section: Quantitative Researchmentioning
confidence: 99%